The Minimum Wage Once Again:: Critique of Sonn and Lathrop - Block, Walter (2018)
In the view of these authors, the minimum-wage law is practically the best thing that has ever been invented, at least since sliced bread. They maintain that this legislation has led to greater, not less, employment, particularly for low-skilled workers, who might have been expected to lose their jobs, or not attain any in the first place, at least according to the traditional analysis of such laws. The present essay is an attempt to defend the view that this pernicious legislation creates unemployment for the poor, who are the least likely to be able to withstand its deleterious effects.